2017
DOI: 10.7821/naer.2017.7.243
|View full text |Cite
|
Sign up to set email alerts
|

Internet and people with intellectual disability: an approach to caregivers’ concerns, prevention strategies and training needs

Abstract: The aim of this study was to explore caregivers' views about the risks of the Internet for people with intellectual disabilities and their preparation and ability to use prevention strategies to address them. The participants (20 family members and 24 staff members) belonged to a non-profit association working with people with developmental and intellectual disabilities and were asked to respond to a questionnaire about Internet safety and risks. Findings show some concerns from caregivers with regard to the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 16 publications
1
20
0
1
Order By: Relevance
“…First, carers limit or reduce access to the Internet (Chadwick and Wesson 2016) and, second, they control and even censor the online content they can access (Seale and Chadwick 2017). This tendency is relevant because people without disabilities tend to think, on the one hand, that online benefits and risks are greater for people with ID than without ID (Chadwick, Quinn, and Fullwood 2017) and, on the other, that the Internet is an unsafe environment for children and young people with ID (Chiner, Gómez-Puerta, and Cardona-Moltó 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…First, carers limit or reduce access to the Internet (Chadwick and Wesson 2016) and, second, they control and even censor the online content they can access (Seale and Chadwick 2017). This tendency is relevant because people without disabilities tend to think, on the one hand, that online benefits and risks are greater for people with ID than without ID (Chadwick, Quinn, and Fullwood 2017) and, on the other, that the Internet is an unsafe environment for children and young people with ID (Chiner, Gómez-Puerta, and Cardona-Moltó 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…It can be an official noticeboard, a regional information portal, or an e-administration platform if sufficiently sophisticated (Veeramootoo et al 2018). A website should be built with the needs of people with disabilities in mind (Chiner et al 2017;Sohaib et al 2017).…”
Section: Internet Without Barriers-website Accessibilitymentioning
confidence: 99%
“…People with autism may also have challenges with query formulation (Harrysson et al, 2004), making selections from large amounts of text (Harrysson et al, 2004) and navigating vertical structures (Williams and Hennig, 2015), such as result lists. It has also been reported that this group is more exposed to risk (Chiner et al, 2017b) and often has limited access to the web due to overprotection (Chiner et al, 2017a). Moreover, many people with autism may be regarded as silent information seekers, where intermediaries do all the searching on their behalf (Bilal, 2010).…”
Section: Impairments Cohorts Characteristics and Barriersmentioning
confidence: 99%